PEMBUATAN PERTANYAAN AWAL PADA KEGIATAN PRABACA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA INTENSIF - -, Sumarwati; -, Purwadi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2010)
This study aims to improve the quality of the process and product ofintensive reading learning through the use of pre-questions in pre-readingactivities. This study was an action research study conducted in three cycles. Theparticipants were Year VIII students of Class C of SMP Penda Mojogedang,Karanganyar Regency. The results showed that there was an improvement in thepercentage of the students capable of formulating pre-questions, carrying outintensive reading activities appropriately, answering questions correctly with apercentage of 70% at the minimum, and showing active and motivated attitudesduring the learning process. The effective learning procedure was as follows. Thestudents browsed the text, formulated pre-questions with question words 5W +1H, memorized the pre-questions, read the text intensively to find the answers tothe questions, and formulate the answers orally and in writing.Keywords: intensive reading, pre-reading, pre-question